Clinical Manifestations of Herpes Zoster, Its Comorbidities, and Its Complications in North of Iran from 2007 to 2013 - Farhang Babamahmoodi; Ahmad Alikhani; Fatemeh Ahangarkani; Leila Delavarian; Hamidreza Barani; Abdolreza Babamahmoodi (Neurology Research International, 2015)
Background. Herpes zoster infection is a painful worldwide disease. Inappropriate and delayed treatment causes prolongation of the disease with debilitating symptoms and postherpetic neuralgia. Method. A cross-sectional study evaluated shingles cases admitted in a teaching hospital with one-year followup in north of Iran from 2007 to 2013. Results. From 132 patients, 60.4% were male. Head and neck involvement occurred in 78 people (59.1%), thoracoabdominal region in 37 cases (28%), and extremities in 16 cases (12.1%), and one case (0.8%) got multisites involvement. 54 cases (40.9%) had predisposing factors including diabetes mellitus in 26 cases (19.7%), malignancy in 15 (11.4%), immunosuppressive medication in 7 (5.03%), HIV infection in 3 (2.3%), radiotherapy in 2 (1.5%), and tuberculosis in one patient (0.8%). The most common symptoms were pain (95.5%), weakness (56%), fever (31.1%), headache (30.3%), ocular complaints (27.3%), itching (24.2%), and dizziness (5.3%). 21 cases (15.9%) had bacterial superinfection on blistering areas and overall 18 cases (13.6%) had opium addiction. 4 cases (3.03%) died during admission because of comorbidities. Postherpetic neuralgia was reported in 56 patients (42.5%) after three months and seven cases (5%) in one-year followup. Conclusion. Shortening interval between skin lesion manifestation and starting medication can accelerate lesion improvement and decrease disease course, extension, and complication.